Guna-guna / Zaidi Yusof ... [et al.] - Yusoff, Zaidi; Ab. Hamid, Abu Hanifa; Azahar, Muhammad Nizam; Zakaria, Ahmad Adam; Abdul Rahman, Azlan (Universiti Teknologi MARA, Kedah, 2019)
The used materials are casted-off or not consumed and they are usually disposed of. In the Department of Industrial Design, most of the used materials will be collected and then sent to the disposal center. Among the main materials used by the students are the acrylic wood. In order to avoid them from being disposed, it is good to take the approach by collecting all the used materials to be transformed as a trophy for UiTM's internal activities and programs as well as external bookings. This can generate the income of student clubs and students who assist in the work of creating the designs and trophies. The price is based on the design and complexity of the trophy. The trophy is a pioneer project for the use of the used material and will be continued by producing other products under the brand name club for income generating purposes through design using the used materials. Acrylic is also the major component in the production of Industrial Design students and most of the surplus will be disposed-off and wasted. The used woods are then produced as a result of excess student projects reapply to create trophies or souvenirs that can be resold in order to generate student club income.